2019
DOI: 10.1097/ccm.0000000000003627
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Tele-ICU Implementation Based on Observed and Predicted ICU Mortality: A Systematic Review and Meta-Analysis*

Abstract: Objectives: Past studies have examined numerous components of tele-ICU care to decipher which elements increase patient and institutional benefit. These factors include review of the patient chart within 1 hour, frequent collaborative data reviews, mechanisms for rapid laboratory/alert review, and interdisciplinary rounds. Previous meta-analyses have found an overall ICU mortality benefit implementing tele-ICU, however, subgroup analyses found few differences. The purpose of this systematic review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 45 publications
1
34
0
Order By: Relevance
“…Sensitivity analysis has suggested a potentially stronger association with positive outcomes and age of the study ( 8 ). Our own recent systematic review and meta-analysis found that although overall ICU mortality reductions can be expected through tele-ICU intervention, the largest ICU mortality improvements can be expected in ICUs with high preintervention standardized ICU mortality ratios ( 6 ).…”
mentioning
confidence: 99%
“…Sensitivity analysis has suggested a potentially stronger association with positive outcomes and age of the study ( 8 ). Our own recent systematic review and meta-analysis found that although overall ICU mortality reductions can be expected through tele-ICU intervention, the largest ICU mortality improvements can be expected in ICUs with high preintervention standardized ICU mortality ratios ( 6 ).…”
mentioning
confidence: 99%
“…State-of-the-art data collection and analysis goes hand-in-hand with telemedicine, including CCU settings. The value of tele-CCU programmes has been documented 24 25. Another telemedicine application for enhancing 24/7/365 resource availability is teleultrasound 26.…”
Section: Information Technologymentioning
confidence: 99%
“…A recent systematic review 16 led by Fusaro et al evaluated the impact of tele-ICU based on observed and predicted ICU mortality. They included 13 studies (all were pre-post comparisons) with a total of 161,109 patients.…”
Section: Models Of Tele-icu Care and Impact On Patient-important Outcmentioning
confidence: 99%